Antibiotic sensitivity pattern of Staphylococcus aureus from clinical isolates in a tertiary health institution in Kano, Northwestern Nigeria - Nwankwo Emmanuel Onwubiko; Nasiru Magaji Sadiq (The Pan African Medical Journal, 2011)
BACKGROUND: The importance of Staphylococcus aureus as a persistent nosocomial and community acquired pathogen has become a global health concern. It has a remarkable capability of evolving different mechanisms of resistance to most antimicrobial agents. The aim of the present study is to establish the incidence of S. aureus in clinical specimens and its antibiotic sensitivity pattern to various antibiotics in this locality. METHODS: One hundred and fifty consecutive isolates of S. aureus obtained from various clinical specimens between January and December 2009 sent to the Medical Microbiology Laboratory Department of Aminu Kano Teaching Hospital (AKTH) were confirmed by standard bacteriological procedures. Antibiotic sensitivity pattern was carried out by disc diffusion method. RESULTS: The age group with the highest number of isolates was (0-10)yrs while wound infection had the highest frequency of S. aureus isolates (30.7%) in the study. Males (62.0%) were more infected than females (38.0%). The sensitivity pattern of S. aureus to the following antibiotics; Gentamicin, Amoxycillin/clavulanate, Streptomycin, Cloxacillin, Erythromycin, Chloramphenicol, Cotrimoxazole, Tetracycline, Penicillin, Ciprofloxacin, Ofloxacin, Levofloxacin, Ceftriaxone, Amoxycillin and vancomycin were 92.4%, 63.0%, 44.2%, 35.8%, 52.4%, 61.9%, 15.5%, 31.2%, 7.1%, 78.9%, 76.6%, 100%, 71.4%, 30.7% and 100% respectively. Methicillin resistant isolates were sensitive to Levofloxacin 93.7% and Ofloxacin 68.7%. CONCLUSION: The results of the present study show that the fluoroquinolones are effective in the management of Staphylococcus aureus infections including methicillin resistant strains in this environment.